The new myokine myonectin is significantly associated with type 2 diabetes in elderly patients. (14th October 2021) - Leiherer, A; Muendlein, A; Geiger, K; Saely, C H; Larcher, B; Mader, A; Maechler, M; Sprenger, L; Mutschlechner, B; Benda, M; Fraunberger, P; Drexel, H
Abstract: : The novel myokine myonectin is predominantly expressed in skeletal muscle and is involved in the regulation of metabolic homeostasis. A putative association between myonectin and type 2 diabetes mellitus (T2DM) has been discussed controversially in current literature. The purpose of this study was to investigate the association between myonectin and T2DM at different ages. We measured myonectin in 410 vascular risk patients with a mean age of 66 years. Myonectin did not correlate with age (r=−0.19; p=0.697). From our patients 219 (53%) were >65 years, with a mean age of 74 years and 191 ≤65 years, with a mean age of 57 years. The prevalence of T2DM was 40.6% vs. 42.4% in the older as compared to the younger age group. Myonectin concentrations were significantly decreased in elderly patients with T2DM compared to non-diabetic subjects (1.8 vs. 4.2 ng/ml; p=0.002), whereas no significant difference was observed in younger patients (2.6 vs. 2.3 ng/ml; p=0.183). Concordantly, regression analysis revealed an unadjusted odds ratio (OR) of 0.24 [0.07–0.81] (p=0.021) for the association between myonectin and T2DM in elderly patients but not in younger patients (OR=1.08 [0.80–1.45]; p=0.609). The association between myonectin and T2D; remained significant after adjusting for sex, body mass index, LDL cholesterol, HDL cholesterol, current smoking, as well as statin intake in elderly but remained non-significant in younger patients (OR=0.23 [0.07–0.81]; p=0.021 vs. OR=1.05 [0.76–1.46]; p=0.769). We conclude that plasma myonectin levels are significantly associated with T2DM, particularly in elderly vascular risk patients. FUNDunding Acknowledgement: Type of funding sources: None.